Implementasi Sistem Informasi Penjualan Mebel Berbasis Web Menggunakan Metode SCRUM - Bernandika Reyhan Groovytala; Galet Guntoro Setiaji; Ahmad Rifa'i (TIN: Terapan Informatika Nusantara, 2026)
This study focuses on the design and implementation of a web-based furniture sales application at UD. Andhireyma, Boyolali Regency, Central Java Province. The rationale for developing this software stems from the urgent need to optimize efficiency in daily transaction management, product inventory updates, and sales reporting. Involving the active participation of 14 respondents, including business owners, operational staff, and customers, this study adopted the Scrum framework. The methodology’s phases—product backlog, sprint planning, sprint review, and sprint retrospective—were implemented to ensure that system development iterations could dynamically adapt to user expectations. From a technical perspective, the application architecture was built using the PHP programming language and MySQL database management, integrated with HTML, CSS, and JavaScript elements. Comprehensive data collection was conducted through a series of field observations, continuous documentation, and in-depth interviews. Furthermore, to ensure the overall functionality of all features, the Black Box Testing method was strictly applied. Evaluation findings indicate that the implementation of this digital system successfully accelerated and structured the management of commodity data as well as transaction history reports. The risk of manual recording errors was significantly reduced, which directly corresponds to an improvement in the quality and effectiveness of customer service. Based on the successful functional test results, which recorded a success rate of 80%, this e-commerce platform is recommended and deemed highly suitable for immediate implementation in UD. Andhireyma business operations.